PENGARUH PEMBERIAN TEPUNG TONGKOL JAGUNG MUDA HASIL BIODEGRADASI JAMUR TIRAM PUTIH (Pleurotus Ostreatus) DAN ENZIM PEMECAH SERAT TERHADAP KARKAS AYAM PEDAGING - Permatasari, Rani Putri; Hatta, Ummiani; Sugiarto, Sugiarto (FAPETKAN UNTAD, 2017)
The purpose of this study was to determine effect of young corn cob meal as a product of mushroom oyster white (pleurotus ostreatus) biodegradation and breaking fiber enzyme were added in the ration to broiler carcass. This research was implemented in Sigi districts central Sulawesi from June 11 to November 27, 2016. The used chickens is were 175 DOC. This study used a completely randomized design (CRD) with 7 treatments and 5 replication as follows: R0 = 100% control ration, R1 = ration + 5% TTJMF, R2 = ration + 10% TTJMF, R3 = ration + 15% TTJMF, R4 = ration + 5% TTJMF + 7,5% units/kg breaking fiber enzyme, R5 = ration + 10% TTJMF + 7,5% units/kg breaking fiber enzyme, R6 = ration + 15% TTJMF + 7,5% units/kg breaking fiber enzyme. The results of this study showed that the treatment highly significant (P<0.01) to slaughter weight. The treatment showed non significant effect (P>0.05) on carcass percentage as well as the very significant effect (P<0,01) to abdominal fat. It caused of the basic materials used with high fiber feed affected to reduce slaughter weight and abdominal fat. It was concluded that used of TTJMF and breaking fiber enzyme in the ration to the extent 15% + 7.5% units/ kg gived the lowest result on abdominal fat but can not increase the slaughter weight and carcass percentage.Â Keywords: Broiler, corn cob, breaking fiber enzyme, carcass percentage.